Penguatan Bahasa Cinta dalam Proses Pendidikan Karakter bagi Anak Usia Dini - Wismanto, Wismanto; Marni, Susi; Azhari, Mawaddah Warohmah; Sukmawati, Eka (STAI Auliaurrasyidin Tembilahan, 2024)
Character education has become an interesting study in recent years. It is influenced by the failing of the character of children and/or adult into a negative, which is caused by several factors, including technological developments, lack of attention and the presence of parents with children. This study aims to present the use of love language by parents in the process of character education in the Bougenville Perm Complex, West Sidomulyo Village, Tuah Madani District, Pekanbaru City. This study is descriptive-qualitative research. The data in this study were collected using interview, observation, documentation, and FGD techniques. They were then analyzed using a phenomenological analysis model. The results of this study show that parents applied a variety of love languages in cultivating character to their children cultivation, such as physical touch, acts of service, romantic words, giving appreciation in the form of gifts, as well as conditional love language models.